From complex systems to transdisciplinarity : exploring resilience, sustainability, and knowledge integration - Cerro Santamaría, Gerardo del (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"The authors in this book analyze resilience and sustainability in seven different complex adaptive systems (human beings, megaprojects, higher education, food systems, climate change, healthcare settings and cities) by highlighting transitions from complexity to transdisciplinarity as a strategy for knowledge integration. The book also provides insights about the nature of complex adaptive systems based on the cases studied, in particular the issue of second order cybernetics (associated to the mind-matter problematic), the role of entropy in complex systems and the importance of the notion of reflexivity in the current cognitive-reflexive stage in world capitalism. In this way, the book aims at contributing to current debates and objections about the validity of traditional ontological and epistemological positions in the face of radical and rapid transformations worldwide affecting some aspects of capitalist development. The Conclusions explore how complex sustainability needs to integrate several elements beyond the conventional view expressed in the standard, anthropocentric definition of sustainability. The Chapters explicitly criticize current perspectives on capitalism, resilience and sustainability, and the homogenizing aims of some global discourses regarding natures and ecologies. Each Chapter advances a new way forward within a common complexity paradigm. All chapters conceptualize socio-environmental issues by going beyond the nature-culture dichotomy, an effort akin to conjectures developed by contemporary ecological theorists as well as the new materialisms being developed within urban planning and other fields. The Chapters entice readers to relativize and question disciplinary approaches by suggesting new realms to be considered in any study of nature and ecologies, resilience and sustainability. The contributions in this book are important for anyone interested in meaningfully designing research on resilience and sustainability that uses complexity and transdisciplinary perspectives and frameworks"--